Job satisfaction of healthcare workers in Vietnam: A multilevel study. (2nd October 2021) - Quyen, Bui Thi Tu; Lan, Vu Thi Hoang; Minh, Hoang Van
ABSTRACT: This paper aims to assess the level of job satisfaction among healthcare staffs at commune health stations and explore the determinants at the individual and contextual levels. Data on 1, 666 healthcare staffs were extracted from the Vietnam Health Facility Assessment survey 2015. Three levels of linear regression were applied to examine the associations between healthcare staffs' satisfaction and three types of explanatory variables. Results showed that the score of job satisfaction among healthcare staffs was 3.14 points (out of 5). Their age, gender, and education level were significant predictors of their job satisfaction. Healthcare staffs from health facility having higher number of visits per capita and those from poor provinces reported higher level of job satisfaction. Compared to factors at the individual and commune levels, health facility-related factors played a more important role in determining healthcare staffs' satisfaction in Vietnam. Bettering the physical property of CHSs and attracting local people to have health checkups would help increase job satisfaction among healthcare staffs.